Comparative analysis of epigenetic markers in plasma and tissue of patients with colorectal cancer - Kondratov, A.G.; Nekrasov, K.A.; Lototska, L.V.; Panasenko, G.V.; Stoliar, L.A.; Lapska, Y.V.; Kolesnyk, O.O.; Shchepotin, I.B.; Rynditch, A.V.; Kashuba, V.I. (Вiopolymers and Cell, 2014)
Aim. The work is devoted to the development of less invasive tools for the colorectal cancer (CRC) screening. Methods. Q-PCR and methylation-specific PCR techniques were used in the current work. Results. We have shown that the levels of cell-free plasma DNA are higher in the CRC patients compared with the healthy donors (p < 0.01). Hypermethylation of APC, FHIT, LRRC3B and HIC1 genes was studied in the tumor and plasma samples of CRC patients. Two-stage verification for CRC screening was proposed. Conclusions. We proposed and tested a novel approach for CRC screening based on the determination of cell-free DNA and methylated DNA fragments in the plasma.